Informed Consent for Placebo‐Controlled Trials: Do Ethics and Science Conflict?. Issue 5 (1st September 2022) - Feldman, Hope A.; Feldman, James A.; Miller, Charles C.; Walsh, Garrett; Tyson, Jon E.
ABSTRACT: The use of a placebo has been considered the best method for controlling bias in a prospective randomized clinical trial and provides the most rigorous test of treatment efficacy for evaluating a medical therapy. Placebos commonly produce clinically important effects particularly in studies where the primary outcomes are subjective. Yet the potential beneficial or harmful effects of placebos are often not addressed in designing a clinical trial, calculating the sample size, seeking consent, or interpreting clinical trial results. In this manuscript, we use an actual study to indicate three approaches that might be considered in seeking informed consent for placebo‐controlled trials, and we explore the fundamental ethical and scientific complexities involved with each.